Cersei Lannister as a Doctor Faustus: A Todorovian Interpretation of Ambition and Power - Sohan, Riyad Md. Arefin Sohan; Md. Mahmudunnabi Sourov; Sojib Khandaker (English Education Program, Education Faculty, Universitas Nurul Huda, 2025)
This paper explains ambition and power through Tzvetan Todorov’s structuralist model of narrative equilibrium, disruption, and recognition by examining Christopher Marlowe’s Doctor Faustus (1604) and HBO’s Game of Thrones (2011–2019). It interprets how the moral trajectory of ambition as a destructive force transcends medium and era through linking Renaissance humanism with postmodern visual storytelling. Following a qualitative comparative method, this study provides textual and visual analysis of key moments in both works and demonstrates how Faustus and Cersei Lannister embody a shared Todorovian tragic pattern. Updated with recent critical scholarship on narratology and adaptation studies, the research describes that both figures represent the timeless Faustian conflict between desire and ethics. The analysis argues that when ambition is detached from moral equilibrium, it functions as a universal engine of tragedy that sustains the continuity between classical drama and modern television narratives.